Analiza porównawcza nazw centralnych ulic miast Winnica i Iwano Frankiwsk - Stelmaszyk, Dajana; Szymczak, Ewa (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article shows historical and contemporary tendencies in Ukrainian onomastics. The purpose of this paper is to identify differences between street names in Vinnytsia and Ivano-Frankivsk and point out the changes connected with historical events. The main influence on street rename in Vinnytsya had Ukraine's accession to the Soviet Union, German occupation, and the liberation of the city from fascist invaders. However, in Ivano-Frankivsk the most important circumstance was disintegration of the Soviet Union. In article therea are three groups of names classified: memorial names, names connected with history and names connected with geography. The research shows that the biggest part of place names are commemorating names, dedicated to artists, scientists, social and political activists and USSR heroes. The last phenomenon of giving names in honor of USSR heroes is observed only in Vinnytsia, what may be connected with a sense of national belonging which is characteristic for the western part of the country. The smallest number of urbanonyms are geographical names. It should be emphasized that the research is only an experiment as the analysis concerns only selected street names in the cities.